Determinación de los contaminantes atmosféricos emitidos en ladrilleras artesanales en la parroquia Juan Montalvo, cantón Latacunga, provincia de Cotopaxi. - Calvopiña Tapia, Alex Ruben (2018)
At Juan Montalvo Parish of Latacunga Canton, the measurement of atmospheric emissions pollutants emitted by fixed sources, such as brick kilns, was carried out, with the purpose of identify the atmospheric pollutants emitted by them, which were useful to take measurements of mitigation and reduction of atmospheric pollutants, in this way updates and researches were obtained on emissions of polluting gases in this area. For execution of the research job, it was done with the owners of the artisan brick kilns. The identification of each of the sources was taken into account through a geographic reference that allowed exact location of the zones to determine the study area in the parish. In which a fieldwork was carried out, which consisted on gases measurement such as oxygen, carbon monoxide, nitrogen monoxide, nitrogen dioxide, sulfur dioxide and hydrocarbons, through the use of the TESTO 350 gas analyzer equipment Where Carbon Monoxide (CO) data was obtained in all the fixed sources monitored, which are outside the parameters established by the TULSMA regulation Annex VI, Table 1, which is 1800 mg / Nm3. In the same way it was carried out with nitrogen oxide (NOx), 900 mg / Nm3. The generation of carbon monoxide is given by the factors that affect it, the designing of the furnace, the humidity of the fuel (biomass) and its inadequate handling, which generates contamination to the environment and has harmful effects on the health of a person. In this way, a proposal is generated to reduce levels of carbon monoxide (CO), with a new furnace design with new techniques for energy use and fuel management (biomass).